Is it Possible to Successfully Combat Corruption by Scanning Old Rosaries? - A. N. Tsatsulin (Управленческое консультирование)
The article is dedicated to the International Day against Corruption, which is celebrated annually on December 9. Corruption as a complex socio-economic phenomenon is generated by a variety of reasons, most of which have already been identified and subjected to comprehensive analysis. But in Russia, corruption has become monstrous, extremely corrupt local, regional and federal officials mock openly over helpless legislation, the consequences of which are seen in the flight of capital from the country, and in the recession / stagnation of the national economy, and in the tragic events of recent times. In the end, corruption undermines the basis for the economic security of the Russian state and undermines the emerging clusters of the national idea. The author of the material continues to understand the causes of corruption and considers the vital issues of this so far insufficiently successful struggle and inefficient counteraction to corruption phenomena that are found in various areas of life and not only our society but also many other countries. The author also tries to find out how corruption is interpreted in the views of the main world religions — Christianity (partly), Islam and national religion — Judaism. The article gives historical reminiscences and authorial comments on the text fragments of the main written sources of these religions. Judgments about the origins, roots and main causes, of course, of an immoral, harmful and destructive phenomenon — corruption, which deeply impressed the national economies of many developed and most developing countries of the planet, are being voiced. The author cites episodes of corruption from the Scriptures of the world religions, gives his own, sometimes controversial or controversial interpretation. At the end of the article, the author expresses his opinion on measures to combat corruption in the form of three independent conclusions. The author’s attempt to express his attitude to the accumulated experience of the sacred struggle against corruption, which is very contradictory in its quality, boils down to the following: instead of solving a concrete, fixed and described problem, it is attempted to reformulate and belittle its danger through sophisticated connotations.